Gender‐specific co‐activation of arginine vasopressin and the hypothalamic–pituitary–adrenal axis during stress. (20th October 2014) - Kacheva, S.; Kolk, K.; Morgenthaler, N.G.; Brabant, G.; Karges, W.
Summary Objective To study the interaction between copeptin and hypothalamic–pituitary–adrenal (HPA) activation in men and women during hypoglycaemic stress. Design and patients A prospective study in 118 patients (mean age 47·7 ± 13·6 years, n = 52 women) undergoing insulin tolerance testing for suspected pituitary dysfunction. Measurements Serum copeptin was measured in serially collected blood samples and assessed in relation to ACTH, cortisol and other endocrine parameters. Results Symptomatic hypoglycaemia (mean glucose nadir, 1·6 ± 0·5 mmol/l) resulted in a rapid significant increase of serum copeptin. Individuals with impaired pituitary function had lower stress‐induced copeptin levels (median, 6·26 pmol/l) than patients with intact pituitary (8·46 pmol/l, P < 0·001). A weak overall correlation between stress‐induced copeptin and cortisol levels was observed (rs = 0·31, P < 0·001). In female individuals, there was a positive correlation between stress‐induced copeptin and ACTH (rs = 0·47, P < 0·001) or cortisol levels (rs = 0·42, P = 0·002), while in males, no correlation with ACTH levels (rs = 0·03, P = 0·75) and poor correlation with cortisol levels (rs = 0·24, P = 0·045) was observed. Patients with central diabetes insipidus showed lowest baseline (2·20 pmol/l) and stimulated copeptin levels (3·68 pmol/l). Conclusions The data from this study indicate that stress‐induced release of AVP in women, but not in men, is linked to the co‐activation of the hypothalamic–pituitary–adrenal system.